Evaluating Indices for Non-invasive Myocardial Recovery Assessment in LVAD-Supported Heart Failure Patients - Boss, Laurence A.; Lovell, Nigel H.; Stevens, Michael C. (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Accurate assessment of myocardial recovery (MR) under left ventricular assist device (LVAD) support is essential for clinicians to manage heart failure patients. However, current techniques for assessing MR are time-consuming, invasive, and infrequent. Measuring MR using indices derived from LVAD operating data instead provides a potential real-time alternative. Several of these indices for assessing the MR of LVAD-supported heart failure patients were collated from the literature and subject to a comprehensive comparative analysis. The objective of this analysis was to determine the most accurate index for assessing systolic cardiac function under LVAD-support, characterized by maximal end-systolic elastance (E max ), while remaining insensitive to preload & afterload. The indices were compared in computational simulation, utilizing an LVAD + cardiovascular system model to sweep through a large array of E max and resistance conditions. Results demonstrated the index that correlated best with E max , showing the highest accuracy, was the ratio between maximum flow acceleration and flow pulsatility (average R 2 =0.9790). The same index also exhibited the lowest % variation (sensitivity) to preload & afterload (1.32% & 13.53% respectively). However, opportunities for improvement remain among current recovery assessment indices, with this study providing a baseline of performance for potential future indices to improve upon.Clinical relevance- This study presents a potential real-time measure of native cardiac function in LVAD-supported heart failure patients to support patient management and further recovery.